Dielectric Properties of Proline Doped Triglycine Sulpho Phosphate (TGSP) Crystals - John1*, V. Revathi2, K. V. Rajendran2, P.M. Andavan3, A.J. Jeyaprakash Manoharan1, N. Joseph (Journal of Experimental Sciences, 2011)
Effect of amino acid (proline) doping on the dielectric properties of triglycine sulphophosphate(TGSP) has been studied. Pure and proline doped TGSP were grown from aqueous solution by solution growthÃ‚Â  technique at room temperature. The dielectric studies were carried out to identify the phase transition temperature and the dielectric behavior. The present study shows that there is an increase in the Curie temperature for the doped crystals.